2022
DOI: 10.1007/s12325-022-02289-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential Unmet Needs in Acute Treatment of Migraine in Japan: Results of the OVERCOME (Japan) Study

Abstract: Introduction: Using data from the ObserVational survey of the Epidemiology, tReatment, and Care Of MigrainE study in Japan (OVER-COME [Japan]), we describe the current status of the acute treatment of migraine in Japan. Methods: OVERCOME (Japan) was a crosssectional, observational, population-based web survey of people with migraine in Japan (met modified International Classification of Headache Disorders criteria or had a physician

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…More male respondents were in full-time employment than female respondents (80.3% and 43.8%, respectively). As reported previously [ 5 , 13 ], there was evidence of substantial disability, with 20.7% of respondents being in the moderate-to-severe MIDAS categories and 37.4% reporting severe impairment or requiring bed rest. There was also evidence of substantial interictal burden, with 41.5% of respondents in the moderate-to-severe MIBS-4 categories.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…More male respondents were in full-time employment than female respondents (80.3% and 43.8%, respectively). As reported previously [ 5 , 13 ], there was evidence of substantial disability, with 20.7% of respondents being in the moderate-to-severe MIDAS categories and 37.4% reporting severe impairment or requiring bed rest. There was also evidence of substantial interictal burden, with 41.5% of respondents in the moderate-to-severe MIBS-4 categories.…”
Section: Resultssupporting
confidence: 77%
“… Data are n (%) unless otherwise specified a Previously reported [ 5 , 12 ] b Other categories for marital status: single, divorced, separated, widowed, and prefer not to say; married respondents previously reported [ 5 , 12 ] c Survey respondents were included in the migraine cohort if they met the modified ICHD-3 criteria for migraine or reported that a physician had diagnosed them with migraine. The number reported here includes all respondents who reported a diagnosis of migraine (most of whom also met ICHD-3 criteria) d Previously reported [ 12 ] e Previously reported (percentages only) [ 13 ] f Previously reported (percentages only) [ 5 ] g The WPAI-M total daily activity impairment score is the mean percentage of time that daily activities were impaired due to migraine in the previous 7 days ICHD-3 International Classification of Headache Disorders, third edition, MIBS Migraine Interictal Burden Scale, MIDAS Migraine Disability Assessment, SD standard deviation, WPAI-M Work Productivity and Activity Impairment-Migraine …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Japanese researchers have shown growing awareness of the effects of headache disorders on the overall health of the Japanese population [7][8][9][10][11][12][13][14]. These studies have revealed several consequences for people with migraines, including an unmet need for migraine healthcare, increased burden and disability, decreased quality of life, productivity impairment, and employer costs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their global impact, there is a notable gap in comprehensive research focused on the clinical characteristics of patients in these settings, particularly in Japan where the prevalence of headaches is comparable to, if not slightly lower than, that observed in Western countries [2][3][4]. Recent efforts by Japanese researchers have highlighted the societal burden of headache disorders [5][6][7][8][9][10][11][12][13][14], yet studies that systematically investigate the clinical pro les of patients attending specialized headache clinics remain remarkably scarce. This gap limits our capacity to tailor patient care effectively and to devise interventions that meet the unique needs of this patient group.…”
Section: Introductionmentioning
confidence: 99%